Courts of Appeals in the Federal Judicial System : a Study of the Second, Fifth, and District of Columbia Circuits. - Howard, J. Woodford, Jr (Princeton legacy library., 2014)
Courts of Appeals were designed to be a unifying force in American law and politics, but they also contribute to decentralization and regionalization of federal law. Woodford Howard studies three aspects of this problem: first, what binds the highly decentralized federal courts into a judicial system; second, what controls the discretion of judges in making law and policy; and third, how can quality judicial decisions be maintained under heavy-volume pressure. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again ma.